A Store-forward Method for Biosignal Acquisition in Smart Health Care System using Wearable IoT Device - Dany P Kartikasari; Apriyanto Tobing; Adhitya Bhawiyuga; Ari Kusyanti; Nuretha Hevy Purwaningtyas (Universitas Muhammadiyah Malang, 2021)
Smart Health Care System has been developed massively in the last decade. Internet of Things implementation has accelerated the development of smart health technology. Now people have realized the importance of doing independent health monitoring. Supported by more affordable e-health tools, motivation in using the smart health system is increasing. The availability of cloud as storage services triggers demands to always be connected to the Internet. However, there are times when interference occurs so the measurement results cannot be stored in the cloud database properly. The idea of using a store-forward mechanism to overcome the problem of disconnected smart healthcare system is proposed in this paper. From the test results, the data can be sent properly eventhough disconnected status occurs for 30 minutes. Smartwatch’s memory usage has increase 30 percent during temporary storage occupied.